2020
DOI: 10.3389/fbloc.2020.00013
|View full text |Cite
|
Sign up to set email alerts
|

Using Blockchain to Improve Decision Making That Benefits the Public Good

Abstract: Human decision making is often prone to biases and irrationality. Group decisions add dynamic interactions that further complicate the choice process and frequently result in outcomes that are suboptimal for both the individual and the collective. We show that an implementation of a Blockchain protocol improves individuals' decision strategies and increases the alignment between desires and outcomes. The Blockchain protocol affords (1) a distributed decision, (2) the ability to iterate repeatedly over a choice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Cerf et al. [46] designed a decision strategy‐based blockchain protocol that improves alignment among the desires and outcomes of the system. The authors have tested the proposed design system by considering the public goods game.…”
Section: Literature Surveymentioning
confidence: 99%
“…Cerf et al. [46] designed a decision strategy‐based blockchain protocol that improves alignment among the desires and outcomes of the system. The authors have tested the proposed design system by considering the public goods game.…”
Section: Literature Surveymentioning
confidence: 99%
“…Because of distributed ledger technology, the professionals felt more comfortable recruiting and sectioning without the use of incorrect credentials. The complexity of selecting new criteria, such as performance metrics (Kremer, 2018;Pillai and Sivathanu, 2021), employee engagement (Pal et al, 2016), work-life balance (Casino et al, 2019) and employee retention (Hofmann and Stokburger-Sauer, 2017), was the key issue that was challenging to handle with the current technique of maintaining HR records in HRM (Alharby et al, 2018;Cerf et al, 2020;Olivas-Lujan, 2019). Thus, the parameters can be assessed using blockchain, and appropriate decisions can be taken.…”
Section: Market Disruption Potentialmentioning
confidence: 99%
“…Since the decision-maker has direct control over the decision-making process, individual biases or judgment, and rationalization are frequently prevalent in administrative and managerial choices, particularly those involving human resources (Rikken et al, 2019;Tapus and Manolache, 2019;Cerf et al, 2020). Technology plays the key role in solving the issue of individual biases or judgment, and rationalism (Islam et al, 2012).…”
Section: The Role Of Blockchain Technology In Hrmmentioning
confidence: 99%
“…As a potential solution to such group-based operation problems, blockchain has emerged and been employed in common group-based exercises to test its ability to govern such interactions. For example, an experiment that was conducted by Moran Cerf, Sandra Matz, and Aviram Berg, which incorporated its use into a Public Goods game, showed that its use of Smart Contracts allowed operating entities to understand and take opportunities that yielded better results [122]. Under different rule sets, this logical operation could be applied to vehicle systems as well, allowing them to avoid collisions and operate optimally on the road, securing the safety of all group entities and their passengers.…”
Section: Application Of Blockchain In Collective Decisionmentioning
confidence: 99%